VUCA in the present-day health workplace and the mental health and wellbeing of health care workers: a systematic scoping review - Charles Chigoziem Okonkwo; Ezekiel Uba Nwose; Gavin Beccaria; Rasheda Khanam (BMC, 2024)
Abstract Background The health workplace is fraught with fluctuations and uncertainties, creating a volatile, uncertain, complex, and ambiguous (VUCA) environment, particularly impacting frontline healthcare workers (HCWs) and leading to an epidemic of stress, burnout and health issues, exacerbated by the COVID-19 pandemic. Objectives This paper aims to explore the multifaceted aspects of HCWs wellbeing, address challenges arising due to COVID-19 and VUCA and highlight innovative approaches within health systems to enhance the quality of life HCWs. Methods A systematic review was conducted using PubMed and Scopus with search terms including 'VUCA,' 'health personnel,' 'frontline healthcare workers,' and 'psychological wellbeing.' Grey literature focusing on Australia and Nigeria was also included. Search was limited to titles on "COVID-19", articles published in English, and articles published from inception to 11th March 2024. Findings Initial search terms generated hundreds of thousands of literatures but after limitations to titles on COVID-19, 32 articles were screened and 22 selected for critical review. Seven other grey articles were included with focus on Australia and Nigeria. The summary findings indicate the disruptiveness of VUCA, and associated need to improve healthcare workers' resilience and this calls for further research. Conclusion This report highlights the further need to explore the volatile, uncertain, complex and/or ambiguous health workplace with a view to improve healthcare workers wellbeing. Intentional organizational support strategies along with personal coping strategies should be further explored towards improving HCWs resilience and wellbeing.